Gender Equality Perspective in Surah An-Nisa': 34 (A Comparative Study of Tafsir At-Thabari and Tafsir Al-Azhar) - Iqbal, Roihan Muhammad; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Religion is often marked by gender inequality. Gender equality has always been controversial, especially in explaining, interpreting, and determining the law between women and men. At-Thabari and Buya Hamka have similarities and differences in interpreting Surah an-Nisa': 34. This study aims to determine the interpretation of Surah an-Nisa': 34 according to classical and contemporary interpreters At-Thabari and Buya Hamka to find similarities and differences in the interpretations of At-Thabari and Buya Hamka, and to determine the relevance of gender equality in the perspective of Surah an-Nisa': 34. This type of research uses library research. Then, the data was analyzed using a comparative descriptive method, carried out using analysis techniques and comparisons, and the validity of the data was checked to obtain research results following the objectives. The results of this study indicate that At-Thabari and Buya Hamka's thoughts on gender equality have similarities in interpreting Surah an-Nisa': 34 regarding the authority of men over women, and there are differences in thinking based on Surah An-Nisa: 34 regarding the interpretation view. Differences in time, conditions, situations, and civilizations that influence it. Based on this study, it can also be concluded that the surah an-Nisa': 34 emphasizes that Islam, on several occasions, elevates the position of men over women. Gender equality is part of Islamic values that apply universally.